Public health order in French-speaking Africa - (:unkn) unknown (My University, 2017)
Legally, there are several concordant indications clearly highlighting the importance of public health to public order in Francophone Africa. On the basis of this finding, the concept of public sanitary order is based on sound arguments based on its existence and positioning as a dismemberment of the general or traditional definition of public order. On the other hand, the almost fusional link between public sanitary order and the fundamental right to security undermines the relevance of its action in most African states. At issue is the embryonic stage of social security in French-speaking Africa, which contrasts with police measures aimed at the protection of public health, so that protective measures (public health police) and lack of protection (The very low coverage of social security) overlap and contradict each other. Obviously, the combination of these two factors: the inoperability of the right to health and the inefficiency of public services are likely to further weaken the public health order in Francophone African states. Ultimately, in addition to its legal and regulatory justification, public sanitary order in Africa is severely lacking in human, financial, material and institutional means to make it a genuine tool for preserving public health, a component of public order
Keywords: African Research